Optical Constants of UV Transparent EVA and the Impact on the PV Module Output Power under Realistic Irradiation. (August 2016) - Vogt, Malte R.; Holst, Hendrik; Schulte-Huxel, Henning; Blankemeyer, Susanne; Witteck, Robert; Hinken, David; Winter, Matthias; Min, Byungsul; Schinke, Carsten; Ahrens, Ingo; Köntges, Marc; Bothe, Karsten; et al.
Abstract: We measure and discuss the complex refractive index of conventional ethylene vinyl acetate (EVA) and an EVA with enhanced UV-transmission based on spectroscopic ellipsometry, transmission and reflection measurements over the wavelength range from 300-1200 nm. Ray tracing of entire solar cell modules using this optical data predicts a 1.3% increase in short circuit current density ( J sc ) at standard test conditions for EVA with enhanced UV transmission. This is in good agreement with laboratory experiments of test modules that result in a 1.4% increase in J sc by using a UV transparent instead of a conventional EVA. Further, ray tracing simulations with realistic irradiation conditions with respect to angular and spectral distribution reveal an even larger J sc increase of 1.9% in the yearly average. This increase is largest in the summer months with an increase of up to 2.3%.